Analytical solution for the constrained Hansen-Jagannathan distance under multivariate ellipticity - Nikolay Gospodinov; Raymond Kan; Cesare Robotti (Federal Reserve Bank of Atlanta, 2012)
We provide an in-depth analysis of the theoretical properties of the Hansen-Jagannathan (HJ) distance that incorporates a no-arbitrage constraint. Under a multivariate elliptical distribution assumption, we present explicit expressions for the HJ-distance with a no-arbitrage constraint, the associated Lagrange multipliers, and the SDF parameters in the case of linear SDFs. This approach allows us to analyze the benefits and costs of using the HJ-distance with a no-arbitrage constraint to rank asset pricing models.
Keywords: G12; 330; Hansen-Jagannathan distance; no-arbitrage; model ranking; multivariate elliptical distributions